El movimiento corporal en el desarrollo de la expresión oral de los niños y niñas del primer grado de Educación Básica de la Unidad Educativa Fiscomisional San Vicente de Paúl, Cantón Riobamba, Provincia de Chimborazo, año lectivo 2015-2016. - Pilco Aulla, Gabriela Fernanda (2016)
The research “Body movement in the development of speaking skill of boys and girls of the first grade of Basic Education, was performed at Unidad Educativa Fiscomisional San Vicente de Paul, located in the city of Riobamba, Chimborazo province during the academic term 2015-2016. The aim was developing body movement activities by applying sensory perceptional games, knowledge games and gymnastics in order to develop the oral expression of boys and girls, we started from foundations scientific in philosophical, epistemological, pedagogical, psychological, sociological, axiological and legal, to continue the theoretical framework referring to topics and subtopics related to the independent variable which is the body movement and the dependent variable is the development of oral expression. The methodology, it begins with a quasi-experimental design because the applicability of the tutorial regarding related with the attitude, participation and development of body movement was observed, it is of explanatory type, applied, from the field, bibliographic and descriptive. The method used is the hypothetical - deductive in search from general facts to reach individuals regarding the development of oral language. The technique used was the observation, supported by the observation sheet based on indicators related to the subject. The data obtained through the observation to the boys and girls it was preceded to the tabulation in order to organize with tables and thereby verifying specific hypotheses was made; the alternative guideline refers to the movement of the body and orality by running the sensory perceptional activities, knowledge games and gymnastics with objects in an attempt to strengthen the development of oral expression. The results obtained by the applicability of the guide are important because they could identify the organs via the nearby perception of objects in the environment, through games that improved their integration and active participation to take part in the dialogue or the conversation to improve communication and oral expression, improving cognitive and intellectual abilities.